Customer Experience Management: Topology, Antecedents, And Outcome - Abhari, Kaveh (2018)
Academic research on Customer Experience Management (CEM) is still inconclusive although it is an important element in exploring customer experience. This limitation calls for a systematic theorization and operationalization of CEM. To this end, this study employed a sequential mixed-method methodology to identify the CEM topology and its antecedents and outcome in the Malaysian hotel industry. An exploratory study was first conducted to develop this model based on the triangulation between data from a set of best-practice reviews, interviews, and observations. The proposed model was then tested through a survey and analyzed by using structural equation modeling via Smart PLS. This study reconceptualized customer experience in the context of the service industry based on the experiential values that are detectable, memorable, manageable, distinguishable, and personalizable. Accordingly, CEM topology was operationalized as an organizational competency to manage experiential values co-creation (emotional, sensorial, behavioral, intellectual, relational, and interactional values). Customer relationship management, employee experience management, innovation management, and experiential marketing were identified as the key antecedents and marketing performance as the main outcome. The findings revealed the relative importance of the CEM antecedents. Apparently, CRM drives behavioral, relational and interactional experience management whilst innovation management drives emotional, sensorial and intellectual experience management.